The Routledge handbook of the Cold War - Daigle, Craig; Kalinovsky, Artemy M. (Routledge handbooks, 2014)
The Routledge Handbook of the Cold War draws on the wealth of new Cold War scholarship, bringing together essays on a diverse range of topics such as geopolitics, military power and technology and strategy. The chapters also address the importance of non-state actors, such as scientists, human rights activists and the Catholic Church, and examine the importance of development, foreign aid and overseas assistance.